**Show that (ยฌ๐ โถ ๐
) โง (๐ โ ๐) โบ (๐ โจ ๐ โจ ๐
) โง (๐ โจ ยฌ๐ โจ ๐
) โง (๐ โจ ยฌ๐ โจ ยฌ๐
) โง (ยฌ๐ โจ ๐ โจ ๐
) โง (ยฌ๐ โจ ๐ โจ ยฌ๐
).**

The **Answer to the Question**

is below this banner.

**Here's the Solution to this Question**

It follows that

$(ยฌ๐ \to ๐ ) โง (๐ โ ๐)$

$โบ(\neg\neg๐ \lor ๐ ) โง (๐ \to ๐) โง (P \to Q)$

$โบ(๐ \lor ๐ ) โง (\neg ๐ \lor ๐) โง (\neg P \lor Q)$

$โบ(๐ \lor F\lor ๐ ) โง (\neg ๐ \lor ๐\lor F) โง (\neg P \lor Q\lor F)$

$โบ(๐ \lor (Q\land \neg Q)\lor ๐ ) โง (๐\lor\neg ๐ \lor (R\land\neg R)) โง (\neg P \lor Q\lor (R\land\neg R))$

$โบ(๐ \lor Q\lor ๐ ) โง (๐ \lor \neg Q\lor ๐ ) โง(๐\lor\neg ๐ \lor R) โง(๐\lor\neg ๐ \lor \neg R) โง (\neg P \lor Q\lor R) โง (\neg P \lor Q\lor \neg R)$

$โบ (๐ โจ ๐ โจ ๐ ) โง (๐ โจ ยฌ๐ โจ ๐ ) โง (๐ โจ ยฌ๐ โจ ยฌ๐ ) โง (ยฌ๐ โจ ๐ โจ ๐ ) โง (ยฌ๐ โจ ๐ โจ ยฌ๐ ).$